Prognostic Significance of Six-Month Estimated Glomerular Filtration Rate in Cadaveric Renal Transplantation - 蔡孟昆(Meng-Kun Tsai); 胡瑞恆(Rey-Heng Hu); 李俊仁(Chun-Jean Lee); 李伯皇(Po-Huang Lee) (Journal of the Formosan Medical Association, 2005)
We hypothesized a linear relative-risk model for graft survival of cadaveric renal transplantation, with a 6-month estimated glomerular filtration rate (GFR) employed as the linear parameter quantifying functioning renal mass and the detrimental effects of early chronic allograft nephropathy. A retrospective study was conducted in a 15-year series of cadaveric renal transplantations (n = 227) with cyclosporin-based immunosuppression in a single transplant center. The Cockcroft-Gault formula was used for estimation of GFR, with a correction factor of 0.85 used for women. Stepwise Cox's regression analyses were applied to examine the prognostic significance of the 6-month estimated GFR. The Kaplan-Meier 5- and 10-year graft survival rates for this study were 80.67% and 59.43%, respectively. From univariate analysis, recipient gender, acute rejection and 6-month estimated GFR were significantly associated with graft survival (p < 0.05). Acute rejection became less significant (p = 0.0033) than 6-month estimated GFR (p = 0.0001) when 6-month estimated GFR was introduced in the stepwise regression procedures. We demonstrated that 6-month estimated GFR is a significant prognostic indicator in cadaveric renal transplantation and is an essential parameter in the regression modeling of long-term graft survival.